Cell Cycle Changes, DNA Ploidy, and PTTG1 Gene Expression in HTLV-1 Patients - Levy, Debora; Ferreira, Mari Cleia M. R.; Reichert, Cadiele O.; de Almeida, Lis Vilela; Brocardo, Graciela; Lage, Luis Alberto P. C.; Culler, Hebert F.; Nukui, Youko; Bydlowski, Sergio P.; Pereira, Juliana (Frontiers in Microbiology, 2020)
Human T-cell lymphotropic virus type-1 (HTLV-1) is a pathogenic retrovirus that is associated with adult T-cell leukemia/lymphoma (ATL). Genetic instability is the hallmark of ATL. Cell cycle progression is needed for virus particle reproduction. HTLV-1 encoded Tax protein ultimately disrupts the mitotic spindle checkpoint, leading to incorrect chromosome segregation, resulting in aneuploidy. Cell cycle abnormalities have been described in T cells transfected with HTLV-1 virus in vitro, but not in HTLV-1 asymptomatic carriers. PTTG1 and HTLV-1 viral protein Tax exhibit a cooperative transforming activity. Overexpressed PTTG1 results in chromosome instability and aneuploidy, which has been suggested as a mechanism underlying PTTG1 transforming activity. Here we aimed to investigate cell cycle, DNA ploidy and PTTG1 mRNA expression in CD4+ and CD8+ T cells in healthy subjects (HS), HTLV-1 asymptomatic carriers and ATL patients. We have identified that HTLV-1 asymptomatic carriers have shown DNA aneuploidy and cell cycle arrest at cell cycle phase G0/G1 in CD4+ T cells. CD8+ T cells of HTLV-1 asymptomatic carriers also demonstrated DNA aneuploidy but without alteration in cell cycle. In ATL, CD4+ and CD8+ T cells present a higher number of cells in cell cycle S-phase and PTTG1 overexpression. These studies provide insight into malignant transformation of HTLV-1 asymptomatic carriers to ATL patients.